The Effects of Xanthorrhizol on the Morphology of Candida Cells Examined by Scanning Electron Microscopy - YAYA RUKAYADI; JAE-KWAN HWANG (Indonesian Society for microbiology, 2007)
The effects of xanthorrhizol, a natural anticandidal agent isolated from the rhizome of temulawak or java turmeric (Curcuma xanthorrhiza Roxb.) on the morphology of four human pathogenic Candida species, i.e., C. albicans, C. glabrata, C. guilliermondii, and C. parapsilosis was examined by scanning electron microscopy (SEM). The SEM analysis showed that, unlike control cells representing normal oval to spherical with smooth surface, treatment of Candida strains with xanthorrhizol at 1 x MICs (minimum inhibitory concentration) significantly affected the external morphology, exhibiting deformation, and protrusions on the cell surface. The potent anticandidal activity of xanthorrhizol may support the use of medicinal plants for the treatment of candidal infections.